Pengendalian Run-Off Dengan Sumur Resapan Di Kawasan Kampus Universitas Andalas Limau Manis Kota Padang (Studi Kasus Politeknik Negeri Padang) - Tri Intan Putri; Elvi Roza Syofyan; Revalin Herdianto; Prestyo Anggara Lubis (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2019)
Changing the land use of the Limau Manis area from the forest to the campus area can directly reduce water catchment areas, where water cannot soak into the ground, so that water reserves in the ground become reduced and run-off increases. To overcome this problem, an environmental friendly run-off control study was carried out, namely with recharge wells. The purpose of this study was (1) to find out the storage capacity of each infiltration well in the Padang State Polytechnic Campus, (2) to find out the number of infiltration wells to reduce run-off in the Padang State Polytechnic Campus, and (3) to know the effect of levels ground water to changes in infiltration rate. The method used in this study is land use analysis using QGIS. Analysis of rainfall using the Normal, Log Normal, Gumbel and Log Pearson Type III methods. Test the validity and suitability of the distribution with the Chi-Square and Smirnov-Kolmogorof tests. Run-off discharge analysis is calculated using the Rational method. Primary data were obtained by field testing and infiltration well making. The results of this study were (1) the capacity (volume) of storage in each infiltration well was different, where the largest infiltration well volume was 4.6 m3 while the smallest infiltration well volume was 3.1 m3, (2) the number of infiltration wells can reduce run-off varies, with 186 units of infiltration wells reducing by 34.2% runoff discharge to 65.8%, 113 infiltration well units reducing by 20.4% runoff discharge to 79.6%, 60 infiltration well units reducing by 10.8% runoff discharge to 89.2%, and 31 infiltration well units reduce by 5.5% runoff discharge to 94.5%, and (3) changes in groundwater content from 30.6% -50.6% cause a decrease in infiltration rate of 0.1 cm / minute.